The Future of Science in The Hand: A Review Literature of Mobile Learning from 2015-2024 - Fitri April Yanti; Rendy Wikrama Wardana; Hayuni Retno Widarti; Ahmad Walid; Rita Sartika; M. Anas Thohir (Journal of Natural Science and Integration, 2025)
This study investigates trends in mobile learning based on data from international publications. Data were collected from the Scopus database covering the period 2015–2024, resulting in a total of 174 selected articles. A systematic literature review (SLR) was employed to synthesize ideas, findings, and knowledge in an academic-oriented framework. The study aimed to analyze annual publication trends, leading contributing countries, targeted skills, educational levels adopting mobile learning, and technologies or applications supporting mobile-based science education. The findings indicate a notable increase in publications in 2020, with the United States contributing the largest share of research. Technologies and applications supporting science learning primarily included virtual reality (VR), augmented reality (AR), and STEM-oriented tools. Mobile learning was found to enhance skills such as conceptual understanding, digital literacy, and science process skills. Among educational levels, mobile learning was most widely implemented in higher education, followed by elementary, middle, and secondary schools. Overall, mobile learning demonstrates potential in fostering essential skills within science and technology education. These findings can inform future strategies and innovations for the effective integration of mobile learning in science curricula.Keywords: mobile learning, science learning, educational skills, learning methods, education level.